The kinetics and mechanism of filiform corrosion affecting organic coated Mg alloy surfaces - Christos Kousis (Corrosion Science, 2022)
The filiform corrosion (FFC) of organic coated magnesium alloys is investigated using in-situ scanning Kelvin probe and time-lapse photography. FFC is initiated by injecting MgCl2, HCl and FeCl2 into a coating defect and ensuing FFC propagation rates are shown to increase as a logarithmic function of the chloride ion concentration and are strongly dependent on relative humidity. Post-corrosion surface analysis shows chloride abundance near the filament leading edge and evidence of sequestration within corroded regions behind. The FFC mechanism is consistent with chloride-induced anodic dissolution at the front coupling with water reduction on a cathodically-activated corroded surface behind.